2004 International Pipeline Conference, Volumes 1, 2, and 3 2004
DOI: 10.1115/ipc2004-0320
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Toughness Testing of Pipeline Girth Welds

Abstract: The guidelines and recommendations for fracture toughness testing of pipeline girth welds outlined in CSA Z662-03, Annex K are reviewed in this work. In Annex K of CSA Z662-03, the specimen type and notch location have been grouped into four categories and the CTOD tests are to be carried out in accordance with either BSI Standard 7448 or ASTM Standard E 1290. In the present study, CTOD tests have been conducted on a manual shielded-metal-arc weld (SMAW) that was prepared in a high strength X80 pipeline steel.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…Fracture toughness is used in Engineering Critical Assessment (ECA) to assess the fitness‐for‐service of engineering structures with respect to avoidance of fracture . Differences in the values of fracture toughness measurements on the same specimen using different methods could result in a structure being considered safe or not.…”
Section: Introductionmentioning
confidence: 99%
“…Fracture toughness is used in Engineering Critical Assessment (ECA) to assess the fitness‐for‐service of engineering structures with respect to avoidance of fracture . Differences in the values of fracture toughness measurements on the same specimen using different methods could result in a structure being considered safe or not.…”
Section: Introductionmentioning
confidence: 99%
“…The J-R curves used in this study are from six SE(B) specimens tested and reported by Shen et al 18 All the specimens were fabricated from the based metal of a pipe segment that is made of the API X80 steel with the minimum specified yield strength (SMYS) of 550 MPa. The mechanical properties of the steel were determined by Shen et al 18 using flattened coupons extracted along the longitudinal direction of the pipe segment. The average values of Young's modulus E, yield strength σ y and ultimate strength σ UTS were reported to be 207 GPa, 568 MPa, and 675 MPa, respectively.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…). Chao and Zhu 9 as well as Zhu and Jang 10 developed the constraint-corrected J-R curve based on J-R curves experimentally determined from a set of SE(B), C(T) and SE(T) specimens tested by Joyce and Link, 16 whereas Zhu and Leis 7,17 developed the constraintcorrected J-R curve based on six SE(B) specimens with different crack lengths tested by Shen et al 18 Zhu and Jang 10 and Zhu and Leis 7 employed the constraint parameter Q to develop the constraint-corrected J-R curves, whereas Chao and Zhu, 9 Lam et al, 19 Zhu and Leis 17 and Wang et al 20 constructed the constraint-corrected J-R curves in terms of the constraint parameter A 2 .…”
mentioning
confidence: 99%
“…This means that the parent steels often have fine grain size and high fracture toughness. There was no significant difference in CTOD for the weld metal, whereas for the HAZ higher CTOD values were found for the 6 o’clock position [ 2 ]. Thus, further post-test fractography and metallography are required to determine the precise microstructures [ 3 ].…”
Section: Introductionmentioning
confidence: 99%